Avian Website Resources - Welte, Sallie; Miller, Erica (Wildlife Rehabilitation Bulletin, 2005)
The following websites have been useful to the authors and contain a wide variety of information on various species of birds. These resources can be invaluable to rehabilitators receiving a new species or seeking additional information on one more familiar. Several are also sites for specialized avian–related supplies or have links to such suppliers.